The Effect of Dantonic Pill on β-Catenin Expression in a Rat Model of Streptozotocin-Induced Early Stage of Diabetic Nephropathy - Zhou Shuhong; Lv Hongjun; Cui Bo; Xu Li; Shi Bingyin (Journal of Diabetes Research)
Diabetic nephropathy (DN) is one of the most common causes of end-stage renal failure. This study was performed to determine the effect of Dantonic Pill (DP) treatment on β-catenin expression in a rat model of streptozotocin- (STZ-) induced early-stage DN, with irbesartan treatment as a positive control. Including an analysis of the general metabolic index and renal function, immunohistochemical staining and reverse transcription real-time PCR for β-catenin were performed in the renal cortex of the rat models every 4 weeks. After the treatments of DP and irbesartan, the albuminuria level, kidney weight/body weight, and thickness of the glomerular basement membrane were decreased, but the expression of β-catenin was not downregulated in the renal cortex. The effective drug target of DP to ameliorate albuminuria and renal hypertrophy should not inhibit the upregulated expression of β-catenin in rats with STZ-induced early-stage diabetic damage.